Microbial ecology and functionality in deep Fennoscandian crystalline bedrock biosphere - Purkamo, Lotta (Helsingin yliopisto, 2015)
Microbial life in the deep subsurface contributes significantly to overall biomass on Earth. Although the microbial communities inhabiting the deep subsurface are abundant, little is known about their diversity, activity, interactions and role in global biogeochemical cycles. The diversity of microbial life in the deep terrestrial subsurface of the Fennoscandian shield was studied with molecular biological methods. The Outokumpu Deep Drill Hole provides access to crystalline bedrock fluids that are estimated to be tens of millions of years old. Characterization of the indigenous bacterial and archaeal communities in addition to microbial communities with important functional properties in bedrock fluids was done from a depth range of 180 m to 2300 m. Microbial community profiling and assessment of possible functional processes was done with molecular fingerprinting, cloning and sequencing methods combined with suitable statistical and bioinformatics analyses. Low cell numbers but high diversity was characteristic to the microbial communities of the Outokumpu deep subsurface. The microbial communities in the fracture zones had in general fewer cells than those in the mixed fluids of the drill hole. Comamonadaceae, Peptococcaceae and Anaerobrancaceae were prevalent bacterial members of the microbial communities in the fracture fluids. Archaea were a minority in microbial communities. Sulfate-reducing bacteria and methanogens were detected at several depths. Microbial communities resembled those detected from other deep Fennoscandian Shield subsurface sites. Furthermore, sulfate reducing communities and archaeal communities resembled those found from the deep subsurface of South Africa. Investigation on carbon assimilation strategies of the microbial communities revealed that mainly heterotrophic Clostridia were responsible for CO2 fixation in this habitat. Representatives of Burkholderiales and Clostridia formed the core microbial community and these were also identified to be the keystone genera. The microbial ...